The spatial impact mechanism and policy spillover of carbon emission trading pilot policy on regional industrial energy efficiency-a case study of China - Li, Jinqiu; Ding, Youqiang; Zhang, Meiling (Frontiers in Environmental Science, 2025)
In response to the pressing energy crisis, China embarked on a comprehensive pilot program for carbon emissions trading in 2013, experimenting with this mechanism across seven provinces and cities, focusing on high-carbon emitting industries. The aim is to leverage carbon pricing through emissions trading to propel China towards its “dual carbon” targets. Drawing on carbon market data spanning 2008 to 2019, this study introduces definitions for industrial single-element and green complex-element energy efficiency. It then investigates the influence of carbon emission trading pilot policy on these two different kinds of regional energy efficiency, utilizing non-spatial panel model, system GMM model, and spatial panel model. Furthermore, the study employs a dynamic spatial Dubin model to delve into the spatial implications and policy spillovers of carbon trading on these efficiency metrics. The finding reveals that carbon emissions trading policies bolster both kinds of regional energy efficiency and exhibit policy spillover effects. However, the immediate and long-term impacts of these policies vary. Specifically, carbon trading enhances single-element energy efficiency in pilot regions by optimizing industrial structures and energy consumption patterns. Meanwhile, it elevates the green complex-element energy efficiency through increased openness and a higher proportion of tertiary industries. Based on these insights, the paper offers a set of policy recommendations.